2006
DOI: 10.1021/jp0573339
|View full text |Cite
|
Sign up to set email alerts
|

STM Study of the Conformation and Reaction of Long-Chain Haloalkanes at Si(111)-7 × 7

Abstract: Scanning tunneling microscopy (STM) has been used to study the adsorption of 1-fluoro-, 1-chloro-, and 1-bromo-substituted C(12) alkanes at the Si(111)-7 x 7 surface, at temperatures from 300 to 500 K. We report self-assembly of these physisorbed adsorbates, C(12)H(25)X, to form approximately circular corrals, (C(12)H(25)X)(2), with charge transfer to a corralled adatom in each case (cf. Dobrin et al. Surf. Sci. 2006, 600, L43). The corrals comprised pairs of semicircular horizontal long-chain molecules stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The formation of the dimers was found to be energetically favorable. Furthermore, molecular dimers formed on the Si(1 1 1)-7 · 7 surface due to dispersion forces have been observed recently [16][17][18].…”
Section: Resultsmentioning
confidence: 88%
“…The formation of the dimers was found to be energetically favorable. Furthermore, molecular dimers formed on the Si(1 1 1)-7 · 7 surface due to dispersion forces have been observed recently [16][17][18].…”
Section: Resultsmentioning
confidence: 88%
“…This is consistent with a transition state in which, even for horizontal adsorbates, the alkyl group is distant from the surface (see below). The exceptions were 1‐chlorododecane and 1‐bromododecane for which the horizontal state occasionally gave alkyl attachment to the surface 6e,f. These dynamics on Si(111) contrast with the dissociative attachment on Si(100), where both the halogen atoms and the alkyl groups were invariably found bound to the surface 10.…”
Section: Comparison Of Measured Activation Energies For V and H Statementioning
confidence: 99%
“…Studies in this laboratory of the adsorption and reaction of haloaromatics5 and haloalkanes6 at silicon surfaces, using scanning tunneling microscopy (STM), provided evidence of vertical, v , and horizontal, h , states of single adsorbates at Si(111)‐7×7; examples being 1‐bromopropane,6a,b 1‐bromopentane,6c 1‐chlorododecane,6df and 1‐bromododecane 6e,f. Experimentally, the assignment of adsorbate alignment ( v vs h ) is based on contrasting surface mobilities6af ( v more mobile than h ) and sometimes differing STM imaging6ac ( v higher than h ).…”
Section: Comparison Of Measured Activation Energies For V and H Statementioning
confidence: 99%
“…As the on-surface bottom-up engineering for novel organic nanoarchitectures with specific electronic properties, molecular self-assembly has received tremendous attention for decades. With its atomic resolution, scanning tunneling microscopy (STM) has been proven to be a powerful tool to visualize the nanometer-scale self-assembled structures, giving us a better understanding of the nature of self-assembly phenomena on atomically flat conductive surfaces. It has been widely reported that two-dimensional (2D) self-assembled supramolecular architectures can be tailored by exploiting intermolecular interactions, including molecule–molecule, molecule–solvent, and molecule–substrate interactions. In addition, designing building blocks and external condition changes (such as solvent and concentration) have been demonstrated to play crucial roles in the formation of 2D nanostructures. In the field of noncovalent interactions, hydrogen bonding is widely studied for its crucial role in the expression of structural polymorphism. As a weak noncovalent interaction similar to hydrogen bonding, halogen bonding, used extensively in three-dimensional (3D) crystal engineering, has been considered as an appealing tool in 2D molecular self-assembly in recent years. In general, halogen bonding that resulted from polarizability of the halogen atom along the C–X axis plays a crucial role in the construction of such 2D self-assembled structures. To the best of our knowledge, the effects of different halogen substituents in the 2D self-assembly have rarely been investigated. In previous studies, since the positive potential of the σ-hole along the C–X axis decreased in the order I > Br > Cl > F = 0, the tiny change of halogen substituents can drastically affect the formation of 2D nanoarchitectures, such as lattice matching, diversity, , type of adsorption, and degree of order . However, the internal mechanism of different halogen substituents affecting the self-assembled structure still remains obscure.…”
Section: Introductionmentioning
confidence: 99%